2022
DOI: 10.21608/ejnsr.2022.247056
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Nurses’ Awareness Regarding Protective Child Advocacy and Rights in the Hospital

Abstract: Advocacy is explained in concrete acts such as helping the patient access needed healthcare facilities, assuring the quality of treatment, defending the patient's interests, and acting as a coordinator for the patient and the health care environments. Aim: Assess pediatric nurses' awareness regarding protective child advocacy and rights in the hospital. Method: A descriptive exploratory research design was utilized, and a convenient sample of 103 nurses at the in-patient pediatric ward, neonatal intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…Our findings emphasize the need for targeted educational initiatives for nursing staff to address identified knowledge gaps. This is consistent with prior research that reported a positive relationship between education and awareness of patients' rights among nursing staff (Khademi et al, 2019;Zaitoun et al, 2021;Mohamed et al, 2022). Nonetheless, our study diverges from the findings of T.K.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings emphasize the need for targeted educational initiatives for nursing staff to address identified knowledge gaps. This is consistent with prior research that reported a positive relationship between education and awareness of patients' rights among nursing staff (Khademi et al, 2019;Zaitoun et al, 2021;Mohamed et al, 2022). Nonetheless, our study diverges from the findings of T.K.…”
Section: Discussionsupporting
confidence: 89%
“…The study suggests that nursing staff in government hospitals might benefit from such educational programs. It recommends educating nursing staff on patients' right to know the identity and qualifications of healthcare providers, consistent with previous research identifying this as a deficiency among nursing staff regarding patients' rights (Mohamed et al, 2022). Additionally, the study underscores the importance of protecting patients' property from theft, damage, and loss, a fundamental aspect of patients' rights that nursing staff must be cognizant of to deliver quality care.…”
Section: Discussionsupporting
confidence: 70%